Half-Sibling Incest in Kody Keplinger’s “A Midsummer Nightmare” - Anita Rahmah Dewi; Ismilla Fitara (JELP Journal of English Language and Pedagogy, 2022)
This study discusses the sibling incest phenomenon reflected in Kody Keplinger’s novel A Midsummer Nightmare. The purpose of this study is to reveal the sibling incest factors contained in Keplinger's novel. In conducting this study, there are several theories which are applied in study, namely psychodynamic by Sigmund Freud's and psychoanalysis by Karen Horney. Those theories are suitable for analyze the phenomenon of sibling incest happens, and causing factors of sibling incest in line of the research problems that has been formulated in this study. The writer also applies context-oriented approach by Mario Klarer to obtain the adequate data. In collecting data, the writer conducts some steps namely, close reading, documenting data, and taking notes, while in analyzing data the writer conducts deep analyzing, describing, and presenting data. Therefore, the writer can identify the phenomenon of sibling incest happens, and several factors for the occurrence of sibling incest in the novel A Midsummer Nightmare by Kody Keplinger, such as (1) between age peers, (2) the law of homogamy, (3) genetic sexual attraction (GSA). Furthermore, The results of this study indicates that this novel attempts to reflect the phenomenon of sibling incest through the character of Natan and Whitley who have problems in their life that lead them to forbidden love. Good parenting and upbringing will help shape the child’s personality to grow well. Love and full attention can make a child find a good way of life. In this novel, the sibling incest factors mentioned above describe a daughter who lacks love and attention from her parents due to the broken home that befell her family, so that she grows up by bad personalities and even love her own brother and having sex for many times.